Increased risk of systemic lupus erythematosus in pregnancy-induced hypertension: A nationwide population-based retrospective cohort study. Issue 30 (July 2016) - Lin, Li-Te; Wang, Peng-Hui; Tsui, Kuan-Hao; Cheng, Jiin-Tsuey; Cheng, Jin-Shiung; Huang, Wei-Chun; Tang, Pei-Ling; Hu, Li-Yu
Abstract : Abstract: Dysregulation of the immune system plays a role in the pathogenesis of both, pregnancy-induced hypertension (PIH) and systemic lupus erythematosus (SLE). It is well known that SLE predisposes to be complicated with PIH. However, few studies have attempted to investigate whether PIH increased subsequent SLE risk. The objectives of this study were to assess the association between PIH and subsequent SLE risk and identify predictive risk factors. Patients with newly diagnosed PIH were selected from the Taiwan National Health Insurance Research Database (NHIRD) and compared with a matched cohort without PIH based on age and the year of delivery. The incidence of new-onset SLE was evaluated in both cohorts. The overall observational period was from January 1, 2000 to December 31, 2013. Among the 23.3 million individuals registered in the NHIRD, 29, 091 patients with PIH and 116, 364 matched controls were identified. The incidence of SLE was higher among patients with PIH than in the matched controls (incidence rate ratio [IRR] = 4.02, 95% confidence interval [CI] 3.98–4.05, P < 0.0001). The IRR for subsequent SLE development remained significantly higher in all stratifications during the follow-up years. The multivariate Cox regression model was performed and the results showed that PIH may be an independent risk factors for the development of subsequent SLE (hazard ratio [HR] = 2.87, 95% CI 2.07–3.98, P < 0.0001). Moreover, multivariate Cox regression model was used again among the PIH cohort only in order to identify the possible risk factors for subsequent SLE in the population with PIH. Patients with PIH may have higher risk of developing newly diagnosed SLE than those without PIH. In addition, among individuals who have experienced PIH, those younger than 30 years, having experienced preeclampsia/eclampsia, single parity, preterm birth, or chronic kidney disease, may display an increased subsequent risk of SLE.